Juridical Protection For Debitors From Execution Of Other Fidusion Garanties As Particular To Credit - Anindita (Fakultas Hukum Universitas Widya Mataram, 2024)
Following the decision of the Constitutional Court No. 18/Law-XVII/2019, The execution of the security of the trust is no longer carried out unilaterally by the creditor by concluding unilaterally that there has been a breach of the promise on the trust security agreement. The ruling of the MK as a form of legal protection of the debtor's rights which are often neglected and deprived by the creditor by concluding unilaterally that debtor has been discharged. Thus, the execution of the security of the trust and the declaration of the debtor is no longer unilaterally carried out by the creditor, unless there is agreement between the creditor and the debtor, or there is a judgment of the court, which states that a debtor has lawfully committed an offence or a misconduct, so that the creditor or funding agency can enforce the security of the trust. The method of research used approach using the method of regulation of legislation linked to the formulation of the problem discussed in it. Next, the author uses a method of approach using a legislative approach. The benefits of this research are expected to add to the scientific expertise especially in the field of civil law in the execution of security trusts.